2018
DOI: 10.1111/jne.12572
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin neurones in the posterodorsal medial amygdala modulate sexual partner preference and anxiety in male mice

Abstract: The posterodorsal medial amygdala (MePD) is a neural site in the limbic brain involved in regulating emotional and sexual behaviours. There is, however, limited information available on the specific neuronal cell type in the MePD functionally mediating these behaviours in rodents. The recent discovery of a significant kisspeptin neurone population in the MePD has raised interest in the possible role of kisspeptin and its cognate receptor in sexual behaviour. The present study therefore tested the hypothesis th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 61 publications
(85 reference statements)
0
59
0
Order By: Relevance
“…Our previous study using pharmacological activation of MePD Kiss1 neurones with the DREADD (Designer Receptors Exclusively Activated by Designer Drugs) methodology built upon previous understanding of the facilitatory role of the MePD in sexual behaviour. We showed that stimulating MePD Kiss1 neurones in this way produces a dual result of augmenting sexual partner preference at the same time as attenuating anxiety behaviour in male mice . Furthermore, in studies of men viewing sexual images, i.v.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Our previous study using pharmacological activation of MePD Kiss1 neurones with the DREADD (Designer Receptors Exclusively Activated by Designer Drugs) methodology built upon previous understanding of the facilitatory role of the MePD in sexual behaviour. We showed that stimulating MePD Kiss1 neurones in this way produces a dual result of augmenting sexual partner preference at the same time as attenuating anxiety behaviour in male mice . Furthermore, in studies of men viewing sexual images, i.v.…”
Section: Discussionmentioning
confidence: 86%
“…The finding of extra‐hypothalamic Kiss1 expression and its receptor in the medial amygdala, and more specifically its posterodorsal subnucleus (MePD), has opened up new possibilities concerning its role in reproductive function. Indeed, we have shown that the MePD Kiss1 neurones are a key upstream regulator of pubertal timing, sexual motivation and social behaviour . Moreover, we have discovered through neuropharmacological studies that kisspeptin signalling in the MePD per se robustly regulates hypothalamic GnRH pulse generator frequency, although the underlying neural mechanisms are unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have identified MeA Kiss neurons and the POA as regulators of sexual motivation and behaviour in male rodents [15, 16, 44]. Several studies have identified various neuronal types in the POA as key players in mediating male-typical mating and paternal behaviour including neurons expressing oestrogen receptor alpha [45], progesterone receptor [46], and galanin [47].…”
Section: Discussionmentioning
confidence: 99%
“…Chemogenetic activation of MeA Kiss neurons reduces anxiety and enhances the preference for oestrous females in male mice [15]. Intra-MeA infusions of kisspeptin impact LH levels and lead to increased numbers of ex-copula erections in male rats [16], suggesting that MeA Kiss signalling regulates GnRH release and participates in sexual arousal.…”
Section: Introductionmentioning
confidence: 99%